Solvent-free coating and preparation method thereof

Through solvent-free polyurethane coating, the macromolecular structure of polyurethane is formed by mixing component A and component B, which solves the problem of insufficient aging resistance of existing two-component polyurethane coatings and achieves high weather resistance and adhesion. And green and environmentally friendly.

CN119331499AActive Publication Date: 2025-01-21SHENZHEN DEGU NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411417276.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-21
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The aging resistance of existing two-component polyurethane coatings still needs to be improved.

Method used

Using solvent-free polyurethane coating, component A and component B are mixed with a mass ratio of 1:1. Component A includes polyester polyol, polyether polyol, polyaspartic acid ester resin, and epoxy resin. etc. Component B includes hexamethylene diisocyanate-based biuret polyisocyanate and dicyclohexylmethane diisocyanate, etc., which form the macromolecular structure of polyurethane through chemical reactions to enhance the weather resistance and adhesion of the coating.

Benefits of technology

It significantly improves the aging resistance and adhesion of the paint, avoids the problem of solvent volatilization, and achieves green and environmentally friendly paint performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079789390000081
    Figure BDA0005079789390000081
  • Figure BDA0005079789390000091
    Figure BDA0005079789390000091
Patent Text Reader

Abstract

The invention belongs to the field of coatings, and provides a solventless coating and a preparation method thereof.The solventless coating is prepared from a component A and a component B according to the mass ratio of 1: 1; the component A is prepared from the following components in parts by mass: 45 to 60 parts of polyester polyol, 25 to 35 parts of polyether polyol, 6 to 10 parts of polyaspartic acid ester resin, 2 to 3 parts of epoxy resin, 6 to 8 parts of titanium dioxide, 2 to 5 parts of mica powder, 0.3 to 1 part of a dispersing agent, 0.3 to 1 part of a dewatering agent, 0.6 to 1.3 parts of a catalyst and 2 to 3 parts of a coupling agent; the component B is prepared from hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate according to the mass ratio of (1.5 to 2) to 1. The polyurethane coating is good in aging resistance, free of solvent volatilization, green and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and relates to a solvent-free coating and a preparation method thereof. Background Art

[0002] Polyurethane waterproof coating is suitable for waterproofing of various underground construction projects, such as basements, subways, etc.; it is also suitable for waterproofing of railways, highways, bridges, culverts and tunnels; it can also be used for waterproofing of kitchens, bathrooms, and pools, as well as waterproofing of gaps, wall pipes, downspouts, etc. At the same time, it can also be used for waterproofing of roofs, walls, and other parts of buildings. Polyurethane waterproof coating is mainly made of isocyanate, polyether and other raw materials through addition polymerization to make isocyanate-containing prepolymers, and then processed with catalysts, anhydrous additives, anhydrous fillers, solvents, etc. Some products also use ingredients such as acrylic polymer emulsions, water, defoamers and preservatives to enhance their waterproof performance and construction performance.

[0003] The single-component polyurethane waterproof coatings currently on the market basically react with moisture in the air to cross-link and solidify to form an elastic and dense waterproof membrane. Its basic curing mechanism is that some of the terminal isocyanate (-NCO) groups of the prepolymer in the coating react with moisture to produce carbon dioxide gas and primary amine (-NH2) groups, and the primary amine groups quickly react with the remaining isocyanate groups to form urea bond extension and solidification. Single-component coatings are easy to use and can be used as soon as the lid is opened, reducing the risk of mixing errors. They dry quickly and are suitable for quick construction and small area repairs, but their overall performance is generally not as good as two-component coatings.

[0004] Two-component polyurethane coatings are cured by a mixed reaction of a main agent and a curing agent. They are usually composed of component A, which consists of polyether polyols, fillers, water absorbents, catalysts, functional additives, etc., and component B, which consists of polyisocyanates or prepolymers containing isocyanate groups. However, the aging resistance of existing two-component polyurethane coatings still needs to be improved. Summary of the invention

[0005] The invention provides a solvent-free coating and a preparation method thereof. The polyurethane coating has good aging resistance, no solvent volatilization, and is green and environmentally friendly.

[0006] The technical solution of the present invention is achieved in this way:

[0007] A solvent-free coating comprises a component A and a component B in a mass ratio of 1:1;

[0008] Calculated by weight, the component A includes: 45-60 parts of polyester polyol, 25-35 parts of polyether polyol, 6-10 parts of polyaspartic acid ester resin, 2-3 parts of epoxy resin, 6-8 parts of titanium dioxide, 2-5 parts of mica powder, 0.3-1 parts of dispersant, 0.3-1 parts of dewatering agent, 0.6-1.3 parts of catalyst, and 2-3 parts of coupling agent;

[0009] The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.5-2:1;

[0010] The polyester polyol has a number average molecular weight of 200 to 5000, a hydroxyl value of 200 to 300 mgKOH / g, and a viscosity of 2500 to 10000 mPa·s at 25°C;

[0011] The functionality of the polyether polyol is 2-3, the hydroxyl value is 25-40 mgKOH / g, and the viscosity at 25° C. is 500-1300 mPa.s.

[0012] Preferably, the polyester polyol can be selected from one or more of NGPS-2320, NGPS-260 produced by Zhangjiagang Nanguang Chemical Co., Ltd. or EVONI K Oxyester HS2272 produced by Germany.

[0013] Preferably, the polyether polyol can be selected from one or more of Shandong Bluestar Dongda DL3000D, EP-330NG, and EP-3600.

[0014] Preferably, the hexamethylene diisocyanate-based biuret polyisocyanate has an NCO content of 21.7 to 22.3%;

[0015] Preferably, the hexamethylene diisocyanate-based biuret polyisocyanate can be made from Wanhua Chemical HB-100.

[0016] Preferably, the polyaspartic acid ester resin has an NH equivalent of 277 g / mol, and F420 produced by Shenzhen Feiyang Junyan New Materials Co., Ltd. can be used.

[0017] Preferably, the epoxy resin is a bisphenol F epoxy resin with an epoxy equivalent of 168-175 g / eq, and the DER-354 epoxy resin produced by Dow Chemical of the United States can be used.

[0018] Preferably, the coupling agent is selected from one or two of 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, triethoxy[4-(trifluoromethyl)phenyl]silane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0019] Preferably, the coupling agent is triethoxy[4-(trifluoromethyl)phenyl]silane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:1.6-2.3.

[0020] Preferably, the catalyst is an organic tin catalyst, selected from one or two of dibutyltin dilaurate, stannous octoate and the organic tin catalyst WCAT-S12 of Guangzhou Yourun Synthetic Materials Co., Ltd.

[0021] Preferably, the particle size of the titanium dioxide is 15-30 nm and the specific surface area is 30-50 m 2 / g.

[0022] Preferably, the dehydrating agent is a molecular sieve dehydrating agent, and the D50 of the molecular sieve is 2-4 μm.

[0023] Preferably, the particle size of the mica powder is 600-800 mesh.

[0024] Preferably, the component A further comprises 0.2-0.5 parts of a pigment, and the pigment is selected from one or more of iron oxide red, chrome yellow, iron oxide yellow, iron oxide black, and molybdate chrome red.

[0025] The present invention also provides a method for preparing the above solvent-free coating, comprising the following steps:

[0026] Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 30-50°C, stir, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst and coupling agent, stir again to obtain component A;

[0027] Mix hexamethylene diisocyanate-based biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir to obtain component B;

[0028] Mix component A and component B and stir to obtain a solvent-free coating.

[0029] Preferably, the stirring speed is 1200-2000 r / min, and the time is 30-50 min.

[0030] The working principle and beneficial effects of the present invention are:

[0031] 1. In the present invention, polyester polyol and polyether polyol are the main hydroxyl components, containing a large number of active hydroxyl groups, which can react chemically with the isocyanate groups in component B to form the molecular structure of polyurethane. Polyaspartic acid ester resin has a unique chemical structure, and there is a large steric hindrance on both sides of the amino group in its molecule. This steric hindrance effect can slow down the reaction speed with isocyanate, so that the coating has enough time for coating and leveling during the construction process, improve the wettability of the coating to the substrate, and increase the contact degree between the coating and the substrate;

[0032] In the present invention, the epoxy resin can provide excellent bonding performance, enhance the bonding force between the coating and the substrate, make the coating more firm, and at the same time give the coating good barrier performance, can effectively prevent the penetration of water and corrosive media, protect the substrate from corrosion, and enhance the overall hardness and wear resistance of the coating; and the polyaspartic acid ester resin has excellent light stability and weather resistance, can effectively resist aging caused by ultraviolet radiation, and extend the service life of the coating. Compared with the epoxy resin, the polyaspartic acid ester resin gives the coating better flexibility, so that the coating is not easy to crack under bad weather and mechanical stress, and maintains surface integrity. The polyaspartic acid ester resin is usually derived from renewable resources, is environmentally friendly, and meets the pursuit of sustainable development in the modern coating industry; the epoxy resin and the polyaspartic acid ester resin work synergistically to significantly improve the weather resistance and coating adhesion, so that the solvent-free coating achieves an optimized balance in multiple performance indicators.

[0033] The isocyanate group (-NCO) in hexamethylene diisocyanate biuret polyisocyanate can react with polyols, polyaspartic acid resins, and epoxy resins to form carbamate bonds, thereby connecting the molecules to form a macromolecular structure of polyurethane. Its biuret structure increases the rigidity and stability of the molecule to a certain extent. The cyclic structure of dicyclohexylmethane diisocyanate provides a certain rigidity for the molecule. At the same time, due to the presence of cyclohexyl, the molecule has good weather resistance and chemical resistance. The two isocyanates can be mixed in a certain mass ratio to combine their respective advantages. The mass ratio of the two isocyanates will affect the performance of the coating. The best performance can be obtained by using hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.5-2:1.

[0034] 2. The dispersant in the present invention can make the pigment and filler disperse evenly in the coating system, prevent agglomeration, and improve the stability and coating performance of the coating; the dehydrating agent can remove trace moisture in the raw materials, avoid defects such as bubbles and bulging caused by the reaction of moisture and isocyanate to generate carbon dioxide, and ensure the quality of the coating; the catalyst can accelerate the reaction rate of polyols and isocyanates and control the curing time of the coating; the coupling agent enhances the bonding force between the filler (such as mica powder, titanium dioxide) and the organic resin, thereby improving the overall mechanical properties and aging resistance of the coating.

[0035] 3. Titanium dioxide in the present invention is not only a white pigment, but also can absorb ultraviolet rays to protect the coating from light aging, which is crucial to improving the aging resistance; mica powder has a unique flaky structure, which can form a physical shield in the coating, shielding the damage of sunlight and ultraviolet rays to the paint film, improving the aging resistance of the coating, and at the same time can also inhibit the penetration of corrosive media and improve the anti-corrosion performance of the coating. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The materials used in the following examples and comparative examples can all be purchased from commercial sources.

[0038] Among them, polyester polyol NGPS-2320, with a hydroxyl value of 230±20 mgKOH / g and a viscosity of 2500-4500 mPa.s at 25°C, was purchased from Zhangjiagang Nanguang Chemical Co., Ltd.

[0039] Polyester polyol NGPS-260, with a hydroxyl value of 250±20 mgKOH / g and a viscosity of 6000-9000 mPa.s at 25°C, was purchased from Zhangjiagang Nanguang Chemical Co., Ltd.

[0040] EVONI K Oxyester HS2272, hydroxyl value 215±5 mgKOH / g, viscosity 1300 mPa.s, purchased from Evonik, Germany.

[0041] Polyether polyol DL3000D, functionality 2, molecular weight 3000, hydroxyl value 37-39 mgKOH / g, viscosity 550-600 mPa.s at 25°C, purchased from Shandong Bluestar Dongda.

[0042] Polyether polyol EP-330NG, functionality 3, molecular weight 5000, hydroxyl value 33-35 mgKOH / g, viscosity 800-950 mPa.s at 25°C, purchased from Shandong Bluestar Dongda.

[0043] Polyether polyol EP-3600, functionality 3, molecular weight 6000, hydroxyl value 27-29 mgKOH / g, viscosity 1100-1300 mPa.s at 25°C, purchased from Shandong Bluestar Dongda.

[0044] Hexamethylene diisocyanate biuret polyisocyanate, -NCO mass fraction 21.7-22.3%, purchased from Wanhua Chemical HB-100.

[0045] Polyaspartic acid ester resin, NH equivalent 277 g / mol, was purchased from Shenzhen Feiyang Junyan New Materials Co., Ltd. as F420.

[0046] The epoxy resin is bisphenol F type epoxy resin, epoxy equivalent weight is 168-175 g / eq, and is purchased from Dow Chemical of the United States as DER-354 type epoxy resin.

[0047] The dispersant was purchased from Guangzhou Yourun Synthetic Materials Co., Ltd. as dispersant YRFC-06.

[0048] Titanium dioxide was purchased from Zhejiang Zhiti Nano-Micro New Materials Co., Ltd. as ZT-T06H titanium dioxide with a particle size of 30 nm.

[0049] The mica powder used is the product with 800 mesh particle size.

[0050] The dewatering agent was purchased from Zhengzhou Chaorong Nanomaterial Co., Ltd., a CR-1273 molecular sieve with a particle size D50: 2-4 μm.

[0051] Example 1

[0052] A method for preparing a solvent-free coating comprises the following steps:

[0053] A. Preparation:

[0054] Prepare component A and component B in a mass ratio of 1:1;

[0055] Measured by mass, the component A includes: 45 parts of polyester polyol NGPS-2320, 35 parts of polyether polyol EP-330NG, 10 parts of polyaspartic acid ester resin, 2.5 parts of epoxy resin, 6 parts of titanium dioxide, 5 parts of mica powder, 0.3 parts of dispersant, 1 part of dewatering agent, 0.6 parts of catalyst dibutyltin dilaurate, 1 part of triethoxy [4- (trifluoromethyl) phenyl] silane, 2 parts of γ- (2,3-epoxypropoxy) propyl trimethoxy silane;

[0056] The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.8:1;

[0057] B. Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 40°C, stir at a stirring speed of 1200 r / min for 30 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst, triethoxy [4- (trifluoromethyl) phenyl] silane, γ- (2,3-epoxypropoxy) propyl trimethoxy silane, stir again at a stirring speed of 1500 r / min for 40 min to obtain component A;

[0058] C. Mix hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir at a stirring speed of 1200 r / min for 30 min to obtain component B;

[0059] D. Mix component A and component B and stir at a speed of 800 r / min for 20 min to obtain a solvent-free coating.

[0060] Example 2

[0061] A method for preparing a solvent-free coating comprises the following steps:

[0062] A. Preparation:

[0063] Prepare component A and component B in a mass ratio of 1:1;

[0064] Calculated by mass, the component A includes: 60 parts of polyester polyol NGPS-260, 30 parts of polyether polyol DL3000D, 6 parts of polyaspartic acid ester resin, 2 parts of epoxy resin, 8 parts of titanium dioxide, 2 parts of mica powder, 1 part of dispersant, 0.3 parts of dewatering agent, 1.3 parts of catalyst stannous octoate, and 2 parts of 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;

[0065] The B component is hexamethylene diisocyanate-based biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 2:1;

[0066] B. Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 30°C, stir at a stirring speed of 800 r / min for 20 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, stir again at a stirring speed of 800 r / min for 20 min to obtain component A;

[0067] C. Mix hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir at a stirring speed of 800 r / min for 20 min to obtain component B;

[0068] D. Mix component A and component B and stir at a speed of 800 r / min for 30 min to obtain a solvent-free coating.

[0069] Example 3

[0070] A method for preparing a solvent-free coating comprises the following steps:

[0071] A. Preparation:

[0072] Prepare component A and component B in a mass ratio of 1:1;

[0073] Measured by mass, the component A includes: 50 parts of polyester polyol EVONI K Oxyester HS2272, 25 parts of polyether polyol EP-3600, 10 parts of polyaspartic acid ester resin, 3 parts of epoxy resin, 8 parts of titanium dioxide, 5 parts of mica powder, 0.8 parts of dispersant, 0.5 parts of dewatering agent, 1 part of catalyst WCAT-S12 (Guangzhou Yourun Synthetic Materials Co., Ltd.), 2.5 parts of γ-aminopropyl triethoxysilane, and 0.3 parts of red iron oxide;

[0074] The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.5:1;

[0075] B. Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 50°C, stir at a stirring speed of 1000 r / min for 30 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst, γ-aminopropyl triethoxysilane and red iron oxide, stir again at a stirring speed of 900 r / min for 40 min to obtain component A;

[0076] C. Mix hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir at a stirring speed of 1000 r / min for 30 min to obtain component B;

[0077] D. Mix component A and component B and stir at a speed of 1000 r / min for 20 min to obtain a solvent-free coating.

[0078] Example 4

[0079] A method for preparing a solvent-free coating comprises the following steps:

[0080] A. Preparation:

[0081] Prepare component A and component B in a mass ratio of 1:1;

[0082] Measured by mass, the component A includes: 45 parts of polyester polyol NGPS-2320, 35 parts of polyether polyol EP-330NG, 10 parts of polyaspartic acid ester resin, 2.5 parts of epoxy resin, 6 parts of titanium dioxide, 5 parts of mica powder, 0.3 parts of dispersant, 1 part of dewatering agent, 0.6 parts of catalyst dibutyltin dilaurate, and 3 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane;

[0083] The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.8:1;

[0084] B. Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 40°C, stir at a stirring speed of 1200 r / min for 30 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stir again at a stirring speed of 1500 r / min for 40 min to obtain component A;

[0085] C. Mix hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir at a stirring speed of 1200 r / min for 30 min to obtain component B;

[0086] D. Mix component A and component B and stir at a speed of 800 r / min for 20 min to obtain a solvent-free coating.

[0087] Example 5

[0088] A method for preparing a solvent-free coating comprises the following steps:

[0089] A. Preparation:

[0090] Prepare component A and component B in a mass ratio of 1:1;

[0091] Measured by mass, the component A includes: 45 parts of polyester polyol NGPS-2320, 35 parts of polyether polyol EP-330NG, 10 parts of polyaspartic acid ester resin, 2.5 parts of epoxy resin, 6 parts of titanium dioxide, 5 parts of mica powder, 0.3 parts of dispersant, 1 part of dewatering agent, 0.6 parts of catalyst dibutyltin dilaurate, and 3 parts of triethoxy [4- (trifluoromethyl) phenyl] silane;

[0092] The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.8:1;

[0093] B. Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 40° C., stir at a stirring speed of 1200 r / min for 30 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst and triethoxy [4- (trifluoromethyl) phenyl] silane, stir again at a stirring speed of 1500 r / min for 40 min to obtain component A;

[0094] C. Mix hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir at a stirring speed of 1200 r / min for 30 min to obtain component B;

[0095] D. Mix component A and component B and stir at a speed of 800 r / min for 20 min to obtain a solvent-free coating.

[0096] Comparative Example 1

[0097] A method for preparing a solvent-free coating comprises the following steps:

[0098] A. Preparation:

[0099] Prepare component A and component B in a mass ratio of 1:1;

[0100] Measured by mass, the component A includes: 45 parts of polyester polyol NGPS-2320, 35 parts of polyether polyol EP-330NG, 12.5 parts of polyaspartic acid ester resin, 6 parts of titanium dioxide, 5 parts of mica powder, 0.3 parts of dispersant, 1 part of dewatering agent, 0.6 parts of catalyst dibutyltin dilaurate, 1 part of triethoxy [4- (trifluoromethyl) phenyl] silane, 2 parts of γ- (2,3-epoxypropoxy) propyl trimethoxy silane;

[0101] The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.8:1;

[0102] B. Mix polyester polyol, polyether polyol and polyaspartic acid ester resin, heat to 40°C, stir at a stirring speed of 1200 r / min for 30 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst, triethoxy [4- (trifluoromethyl) phenyl] silane, γ- (2,3-epoxypropoxy) propyl trimethoxy silane, stir again at a stirring speed of 1500 r / min for 40 min to obtain component A;

[0103] C. Mix hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir at a stirring speed of 1200 r / min for 30 min to obtain component B;

[0104] D. Mix component A and component B and stir at a speed of 800 r / min for 20 min to obtain a solvent-free coating.

[0105] Comparative Example 2

[0106] A method for preparing a solvent-free coating comprises the following steps:

[0107] A. Preparation:

[0108] Prepare component A and component B in a mass ratio of 1:1;

[0109] Measured by mass, the component A includes: 45 parts of polyester polyol NGPS-2320, 35 parts of polyether polyol EP-330NG, 10 parts of polyaspartic acid ester resin, 2.5 parts of epoxy resin, 6 parts of titanium dioxide, 5 parts of mica powder, 0.3 parts of dispersant, 1 part of dewatering agent, 0.6 parts of catalyst dibutyltin dilaurate, 1 part of triethoxy [4- (trifluoromethyl) phenyl] silane, 2 parts of γ- (2,3-epoxypropoxy) propyl trimethoxy silane;

[0110] The B component is hexamethylene diisocyanate-based biuret polyisocyanate;

[0111] B. Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 40°C, stir at a stirring speed of 1200 r / min for 30 min, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst, triethoxy [4- (trifluoromethyl) phenyl] silane, γ- (2,3-epoxypropoxy) propyl trimethoxy silane, stir again at a stirring speed of 1500 r / min for 40 min to obtain component A;

[0112] C. Mix component A and component B and stir at a speed of 800 r / min for 20 min to obtain a solvent-free coating.

[0113] The impact resistance, abrasion resistance, artificial weathering resistance and adhesion of the coating were tested according to HG / T5177 2017. The results are shown in Table 1.

[0114] Table 1

[0115]

[0116]

[0117] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A solvent-free coating, characterized in that: The raw materials include component A and component B in a mass ratio of 1:1; Calculated by weight, the component A includes: 45-60 parts of polyester polyol, 25-35 parts of polyether polyol, 6-10 parts of polyaspartic acid ester resin, 2-3 parts of epoxy resin, 6-8 parts of titanium dioxide, 2-5 parts of mica powder, 0.3-1 parts of dispersant, 0.3-1 parts of dewatering agent, 0.6-1.3 parts of catalyst, and 2-3 parts of coupling agent; The B component is hexamethylene diisocyanate biuret polyisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1.5-2:1; The polyester polyol has a number average molecular weight of 200 to 5000, a hydroxyl value of 200 to 300 mgKOH / g, and a viscosity of 2500 to 10000 mPa·s at 25°C; The functionality of the polyether polyol is 2-3, the hydroxyl value is 25-40 mgKOH / g, and the viscosity at 25° C. is 500-1300 mPa.s.

2. A solvent-free coating according to claim 1, characterized in that: The coupling agent is selected from one or two of 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, triethoxy[4-(trifluoromethyl)phenyl]silane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

3. A solvent-free coating according to claim 1, characterized in that: The coupling agent is triethoxy[4-(trifluoromethyl)phenyl]silane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:1.6-2.

3.

4. A solvent-free coating according to claim 1, characterized in that: The catalyst is an organic tin catalyst, which is selected from one or two of dibutyltin dilaurate, stannous octoate and the organic tin catalyst WCAT-S12 of Guangzhou Yourun Synthetic Materials Co., Ltd.

5. A solvent-free coating according to claim 1, characterized in that: The particle size of the titanium dioxide is 15-30nm, and the specific surface area is 30-50m 2 / g.

6. A solvent-free coating according to claim 1, characterized in that: The dehydrating agent is a molecular sieve dehydrating agent, and the D50 of the molecular sieve is 2-4 μm.

7. A solvent-free coating according to claim 1, characterized in that: The particle size of the mica powder is 600-800 meshes.

8. A solvent-free coating according to claim 1, characterized in that: The component A also includes 0.2-0.5 parts of pigment, and the pigment is selected from one or more of iron oxide red, chrome yellow, iron oxide yellow, iron oxide black, and molybdenum chrome red.

9. The method for preparing a solvent-free coating according to claim 1, characterized in that: The following steps are involved: Mix polyester polyol, polyether polyol, polyaspartic acid ester resin and epoxy resin, heat to 30-50°C, stir, then add titanium dioxide, mica powder, dispersant, molecular sieve dehydrating agent, catalyst and coupling agent, stir again to obtain component A; Mix hexamethylene diisocyanate-based biuret polyisocyanate and dicyclohexylmethane diisocyanate, and stir to obtain component B; Mix component A and component B and stir to obtain a solvent-free coating.

10. The method for preparing a solvent-free coating according to claim 9, characterized in that: The stirring speed is 800-1500 r / min and the stirring time is 20-50 min.

Citation Information

Patent Citations

  • Spraying elastomer with high mechanical property

    CN104341580A

  • Polyurethane coating with high solid content and high weather resistance and preparation method thereof

    CN107641450A

  • Waterborne epoxy resin hybrid polyurethane, preparation method and coating material

    CN117050267A

  • Two-component coating composition

    CN117229700A

  • Light-stable solventless polyurethane coating agents and their use

    EP0693512A1

Cited By

  • Epoxy resin-based woodware finish paint and production method thereof

    CN120137484A